Inflammatory Role of TLR-MyD88 Signaling in Multiple Sclerosis - Zheng, Chao; Chen, Jingtao; Chu, Fengna; Zhu, Jie; Jin, Tao (Frontiers in Molecular Neuroscience, 2020)
Multiple sclerosis (MS) is a neuro-autoimmune and neurodegenerative disorder leading to chronic inflammation, demyelination, axonal and neuronal loss in the central nervous system (CNS). However, the pathogenesis of MS remains unclear up to now. Toll-like receptors (TLRs) are a family of type I transmembrane receptors that play a crucial role in the innate immune response. Myeloid differentiation factor 88 (MyD88) is the adaptor of major TLRs. It has been widely considered that TLR-MyD88 signal pathway plays an important role in the occurrence and development of autoimmune disease. The data have revealed that TLR-MyD88 signal may be involved in the pathogenesis of MS and experimental autoimmune encephalomyelitis (EAE), an animal model for MS by regulating the antigen presentation of dendritic cells, the integrity of blood brain barrier (BBB) as well as the activation of T cells and B cells. Here we summarize the role of TLRs and MyD88 in MS and also discuss the possible therapies that based on them.